2020
DOI: 10.1111/1750-3841.15493
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide selection and mechanism for prevention of protein–polyphenol haze formation in beverages

Abstract: Polysaccharides have been considered as a group of promising candidate for preventing the protein–polyphenol haze formation in beverages. In order to select effective polysaccharides to prevent the haze formation, four protein–polyphenol haze model systems were successfully established using two proteins (i.e., gelatin and bovine serum albumin) and two polyphenols (i.e., procyanidin [PC] and epigallocatechin gallate [EGCG]). Among seven common polysaccharides, 0.5 mg/mL pectin, 0.05 mg/mL xanthan gum, and 0.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For example, the binding of pectin by condensed tannins involves hydrophobic interactions and hydrogen bonding ( Watrelot et al., 2013 , 2014 ). Pectin, xanthan, and guar gum also inhibit protein/tannin precipitation ( Wang et al., 2020 ), and an investigation of Arabic gum, pectin, and polygalacturonic acid showed that pectin was the most effective inhibitor of this precipitation ( Soares et al., 2012 ). Thus, several polysaccharides may bind to condensed tannins to reduce astringency.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the binding of pectin by condensed tannins involves hydrophobic interactions and hydrogen bonding ( Watrelot et al., 2013 , 2014 ). Pectin, xanthan, and guar gum also inhibit protein/tannin precipitation ( Wang et al., 2020 ), and an investigation of Arabic gum, pectin, and polygalacturonic acid showed that pectin was the most effective inhibitor of this precipitation ( Soares et al., 2012 ). Thus, several polysaccharides may bind to condensed tannins to reduce astringency.…”
Section: Resultsmentioning
confidence: 99%
“…These polysaccharides, when present in low concentrations: 0.5, 0.05, and 0.01 mg/mL, compete with proteins to bind polyphenols, which decrease protein-polyphenol aggregation; or they can form a ternary complex (protein-tannin-polysaccharide) to increase the solubility of protein-polyphenol systems. This mechanism promotes the reduction of unwanted turbidity in such products [95].…”
Section: Gum Applicationsmentioning
confidence: 99%
“…They are used as adhesive materials in wood-based industry, and obviously, in adhesive industries in general [91]. Gums have applicability in the pharmaceutical area as emulsifiers and reducing agents for suspended particles, laxatives, in the preparation of antiseptics, binders for tablets and pills, and in the cosmetics area (perfume fixers, skin cleansers, and repellents) [92][93][94][95]. Also, in the medical field, gums are used to control osmotic pressure, in addition to having activity against Leishmania amazonensis and antifungal properties [96].…”
Section: Gum Applicationsmentioning
confidence: 99%
“…The ternary complex of protein-polysaccharide-polyphenol can highly influence nutritional and technical functionality. For instance, Wang et al (2020) established that the polysaccharides and protein competed with each other for polyphenols and at low concentration polysaccharides decreased the aggregation of protein-polyphenol and made the ternary complex containing protein-tannin-polysaccharide to enhance the solubility of aggregates of protein-polyphenol. On the other side, at higher concentration of polysaccharide, the excessive polysaccharides attached to proteins to make proteinpolysaccharide precipitates.…”
Section: Introductionmentioning
confidence: 99%